INTER-ETHNIC COMMUNICATION OF TIONGHOA AND INDIGENOUS IN IT’S CONNECTED WITH NATION INTEGRATION POST NEW ORDER IN MAKASSAR - Jeanny Maria Fatimah (Jurnal Ilmu Komunikasi, 2008)
The result of this research shows that relationship between Tionghoa and Makassar eth- nic stated with the relation in its history, diplomatic, working agreement, and business contact among them. The ethnic of Tionghoa in Makassar sticks to their cultural values such as cel- ebrating of Hari Raya Imlek, using of their own having their friends and relatives live in their ethnical atmosphere. Such social interaction with the people of Makassar goes naturally through education particularly within the government educational institution and business activities. Adaptation of the Chinese with ideology is different. Nevertheless, they try to share the under- standing and appreciation of their respective culture. The identity of China ethnic in Makassar is not yet lost its historical and cultural identities.